Study on risk factor analysis and model prediction of hyperuricemia in different populations - Hou, Kaifei; Shi, Zhongqi; Ge, Xueli; Song, Xinyu; Yu, Congying; Su, Zhenguo; Wang, Shaoping; Zhang, Jiayu (Frontiers in Nutrition, 2024)
The purpose of the present study was to explore the influencing factors of hyperuricemia (HUA) in different populations in Shandong Province based on clinical biochemical indicators. A prediction model for HUA was constructed to aid in the early prevention and screening of HUA. Methods: In total, 705 cases were collected from five hospitals, and the risk factors were analyzed by Pearson correlation analysis, binary logistic regression, and receiver operating characteristic (ROC) curve in the gender and age groups. All data were divided into a training set and test set (7:3). The training set included age, gender, total protein (TP), low-density lipoprotein cholesterol (LDL-C), and 15 other indicators. The Random Forest (RF) and Support Vector Machine (SVM) methods were used to build the HUA model, and model performances were evaluated through ten-fold cross-validation to select the optimal method. Finally, features were extracted, and the ROC curve of the test set was generated. Results: TP, LDL-C, and glucose (GLU) were risk factors for HUA, and the area under the curve (AUC) value of the SVM validation set was 0.875. Conclusion: The SVM model based on clinical biochemical indicators has good predictive ability for HUA, thus providing a reference for the diagnosis of HUA and the development of an HUA prediction model.